Outcome of Ph negative myeloproliferative neoplasms transforming to accelerated or leukemic phase. Issue 12 (2nd December 2018) - Mollard, Lise-Marie; Chauveau, Aurélie; Boyer-Perrard, Françoise; Douet-Guilbert, Nathalie; Houot, Roch; Quintin-Roué, Isabelle; Couturier, Marie-Anne; Dagorne, Anaig; Malou, Mohamed; Le Calloch, Ronan; Luycx, Odile; Thepot, Sylvain; et al.
Abstract: Myeloproliferative neoplasms (MPN) are chronic disorders that can sometimes evolve into accelerated or leukemic phases. We retrospectively identified 122 patients with such blastic phases. The overall median survival was four months: 10.2 months for patients treated with intensive treatments compared to three months for best supportive care ( p = .005). Azacytidine, intensive chemotherapies, or allogeneic stem cell transplantation gave the highest median survivals with 9, 10.2, and 19.4 months, respectively. Accelerated phases (AP) had a longer median survival compared to acute leukemia (4.8 months vs. 3.1 months; p = .02). In this retrospective and observational study, we observe that the longest survivals are seen in patients eligible for intensive treatments. Azacytidine shows interesting results in patients non-fit for intensive chemotherapy. Supportive care should probably be restricted to elderly patients and those with unfavorable karyotype. An early diagnosis of AP could also result in a better survival rate.